Research on simplified modeling of large-scale wind farms based on equivalent transfer function and aggregate equivalent - Ding, Ran; Yang, Chun; Mei, Rui; Yang, Hongyu; Ji, Jie; Shi, Qi (Frontiers in Energy Research, 2023)
Introduction: In grid-connected research of large-scale wind farms, the problem of long simulation time exists in the research based on detailed model. In order to realize the fast simulation and grid-connected transient research of wind farm, this paper presents a simplified equivalent model of wind farm based on equivalent transfer function and improved capacity weighting method. Methods: This paper analyzes the mathematical model of wind turbine, corresponding to the strategy of design simplification, and the simplified model is built according to the equivalent transfer function. In addition, this paper considers the equivalent line loss model of collector line, classifies and aggregates the simplified wind turbines, and calculates the equivalent value of the converged wind turbines by using the improved capacity weighting method, the grid-connected simplified modeling of large-scale wind farm is realized. Results: A model of wind farm-MMC-HVDC flexible grid-connected wind power system is built. The simulation results show that the simplified equivalent model improves the simulation speed greatly while guaranteeing the dynamic characteristics. Discussion: The simplified equivalent strategy of wind farm can keep the same dynamic performance with the detailed model, and improve the simulation speed, and realize the fast simulation and grid-connected transient research of wind farm.